An Investigation of Innovative Materials and Technologies for Sustainable Construction in Nigeria - Unegbu, H C O; Yawas, Danjuma Saleh; Dan-asabe, Bashar; Alabi, A.A. (Civil and Environmental Science Journal (CIVENSE), 2024)
This study explores the adoption and effects of innovative materials and advanced technologies on sustainable construction practices in Nigeria. Employing a mixed-methods approach, the research integrates quantitative surveys and qualitative interviews to collect comprehensive data from 255 construction professionals, achieving an 85% response rate. The findings indicate that recycled materials and green concrete are the most frequently utilized innovative materials, primarily due to their environmental advantages and cost-effectiveness. Building Information Modeling (BIM) and prefabrication emerge as the most widely adopted advanced technologies, enhancing efficiency, reducing waste, and improving project quality. Additionally, regression analysis reveals the complex nature of adopting sustainable construction practices, with cost emerging as a significant barrier for many firms. Despite these positive developments, challenges such as high initial costs, lack of awareness, insufficient regulatory support, and limited availability of sustainable materials impede wider adoption. The study highlights the necessity for targeted interventions, including financial incentives, stronger regulatory frameworks, and comprehensive education and training programs, to foster sustainable construction practices. The findings have substantial implications for policymakers, industry professionals, and researchers, offering a foundation for future research and practical strategies to advance sustainability in Nigeria's construction sector.